Surface mechanomyography and electromyography provide non-invasive indices of inspiratory muscle force and activation in healthy subjects - Lozano-García, Manuel; Sarlabous, Leonardo; Moxham, John; Rafferty, Gerrard F.; Torres, Abel; Jané, Raimon; Jolley, Caroline J. (Scientific reports, 2018)
The current gold standard assessment of human inspiratory muscle function involves using invasive measures of transdiaphragmatic pressure (P di ) or crural diaphragm electromyography (oesEMG di ). Mechanomyography is a non-invasive measure of muscle vibration associated with muscle contraction. Surface electromyogram and mechanomyogram, recorded transcutaneously using sensors placed over the lower intercostal spaces (sEMG lic and sMMG lic respectively), have been proposed to provide non-invasive indices of inspiratory muscle activation, but have not been directly compared to gold standard P di and oesEMG di measures during voluntary respiratory manoeuvres. To validate the non-invasive techniques, the relationships between P di and sMMG lic , and between oesEMG di and sEMG lic were measured simultaneously in 12 healthy subjects during an incremental inspiratory threshold loading protocol. Myographic signals were analysed using fixed sample entropy (fSampEn), which is less influenced by cardiac artefacts than conventional root mean square. Strong correlations were observed between: mean P di and mean fSampEn |sMMG lic | (left, 0.76; right, 0.81), the time-integrals of the P di and fSampEn |sMMG lic | (left, 0.78; right, 0.83), and mean fSampEn oesEMG di and mean fSampEn sEMG lic (left, 0.84; right, 0.83). These findings suggest that sMMG lic and sEMG lic could provide useful non-invasive alternatives to P di and oesEMG di for the assessment of inspiratory muscle function in health and disease.